People or Persons?: A Corpus-based Study - Supanfai, Pornthip (rEFLections, 2022)
The study aims to investigate the similarities and differences between nominal synonyms people and persons focusing on collocations and semantic preferences. The data are drawn from the Longman Dictionary of Contemporary English (online version) and the original British National Corpus. The results of the study demonstrate that the two nouns share five statistically significant collocates and five semantic preferences including health, age, employment status, socioeconomic status, and thoughts and feelings. However, they also display distinctive semantic preferences. While people shows semantic preferences for negative actions, numbers, and ethnicity words, persons frequently collocates with words from the semantic set of legislation. The analysis of collocations and semantic preferences also confirms a high degree of formality of persons as indicated in the dictionary. Even so, the corpus data show that despite a high degree of formality, persons is not restricted to formal contexts but can also be used in informal contexts such as fiction.